Asymptotic Properties of Solutions of Functional Differential Equations - Vacková, Jitka, 1981-; Půža, Bedřich, 1949-; Masarykova univerzita. Ústav matematiky a statistiky (2016)
Disertační práce pojednává o různých okrajových úlohách funkcionálních diferenciálních rovnic, zejména o úlohách na ohraničená řešení. Jsou studovány kvazi-lineární okrajové úlohy pro systémy obyčejných diferenciálních rovnic na R+, s využitím Banachovy věty o pevném bodě a metody postupných aproximací pro konstrukci řešení včetně numerické stability, dále jsou studovány podmínky ohraničenosti řešení nelineárních systémů se zpožděným argumentem na R a nakonec jsou uvedena kritéria existence ohraničených řešení pro obecné systémy funkcionálních diferenciálních rovnic s využitím apriorních odhadů a vět o diferenciálních nerovnostech. Ve všech případech jsou odvozena kritéria řešitelnosti a jednoznačné řešitelnosti uvažovaných úloh s použitím různých přístupů.
The doctor thesis provides with an insight into the issue of bounded solutions of functional differential equations. Various boundary problems are considered: quasi-linear boundary value problems for systems of ordinary differential equations on R+ using Banach’s Fixed Point Theorem and a method of successive approximations for constructing the solution including a numerical stability; conditions on boundedness of solutions of nonlinear systems with retarded arguments using a priori estimates and finally existence of bounded solutions of general systems of functional differential equations with use of a priori estimates and theorems on differential inequalities. Criteria of solv- ability and unique solvability are presented for all types of problems with a different approach.
Vedoucí práce: Bedřich Půža
Dizertace (Ph.D.)--Masarykova univerzita, Přírodovědecká fakulta, 2016
Keywords: funkcionální diferenciální rovnice; obyčejné diferenciální rovnice; okrajové úlohy; boundary value problems; functional differential equations; ordinary differential equations; disertace; dissertations